A formação do delegado de Polícia Federal: aspectos éticos e deontológicos - Lima, Janderlyer Gomes de (2024)
Among the institutions that constitute National Public Security, the Federal Police is responsible for the Union’s judicial police and several other preventive duties and administrative controls for the preservation of the Democratic Rule of Law and the benefit of society. Institutionally, it assumes ethics, probity and respect for Human Rights as values, recognizing the permanent training of its members as a guideline. To this end, it has the National Police Academy, a government school responsible for the initial and continuing training of its members. Among the positions in the Federal Police career, the Federal Police deputy stands out hierarchically, being, at the same time, responsible for police management and coordination of the judicial police, so that the exercise of the position requires a critical reflection on one’s own nature, functional act, the causes and consequences of administrative acts within the scope of their duties. Based on the assumption that the initial training provided in Professional Training Courses (ANP) can influence professional actions, this research investigates, through documents, the provision of curricular components relating to ethics, moral and deontological values in training courses carried out by ANP between 2009 and 2022 to assume the position of Federal Police deputy, contextualizing the meanings of the term police, how it is structured and the purpose of the Federal Police in the context of Public Security, discussing the position of Federal Police deputy in its ethical aspect in the thought of the philosopher Immanuel Kant (1724-1804), who, relating reason to freedom and taking this as a presupposition of human emancipation in a praxis governed by duty, has human actions as the object of his moral philosophy, for which it is necessary that the actions have their will directed towards the well-being of humanity out of moral duty, not simply the duty to do something. Thus, this research is bibliographic, documentary and qualitative, with theoretical references based on Immanuel Kant and other scholars of police issues on a national and international basis. As a result, it identified that the Federal Police does not minimize the understanding of professional ethics to the set of prescriptions contained in deontological codes, but relates it to Human Rights, addressing police discretion and the legitimate use of force both directly and transversally throughout the curricular matrices of the Police Training Courses for the position of Federal Police deputy held between 2009 and 2022, in whose curricular components precepts and standards of action emerge that refer to the moral thinking of the ethics of virtues and the ethics of duty. From 2020 onwards, there was a reduction in the course load dedicated to the subject, and in the training courses held in 2022 there was a suppression of the curricular component, with the theme being incorporated into a more comprehensive subject in the curriculum prepared by the National Police Academy. In the end, it suggests the resumption of a specific curricular component of professional ethics and institutional values in professional training courses for the position of Federal Police deputy.